Влияние традиций салтовского гончарного производства на керамический комплекс боршевской культуры Подонья - Колода, В.В. (Степи Европы в эпоху средневековья, 2009)
The paper is devoted to studying the ceramic corpus of the Don Slavs (Borshevo archaeological culture -the 8th - the early 11th AD) and tracing the influence of pottery traditions of Saltov archaeological culture (the mid. 8th - the mid. 10th AD) on this corpus. In this work macrolevel and microlevel analyses were used to seek the outside and inside syncretism.